TAFSIR AYAT DAKWAH SURAT AL-HUJURAAT (49): 13 DAN RELEVANSINYA DALAM PENGEMBANGAN DAKWAH MULTIKULTURAL DI INDONESIA - Masnida; Khotibul Umam; Agung Obianto (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This research will discuss the interpretation of da'wah verses, specifically the Al-Qur'an contained in Surah al-Hujuraat verse 13 and its relevance in the development of multicultural da'wah in Indonesia. What this research wants to illustrate is for all readers to understand that the context of Indonesia with various cultural, religious, ethnic and linguistic backgrounds is appropriate for campaigning for da'wah with a multicultural approach. This research uses qualitative methods with a library research approach. This method relies on the analysis of various written sources such as books, books, journals, articles and other documents that are relevant to the topic under study. Several opinions of scholars such as Ibnu Kathir became references in completing this research. The principle of multiculturalism in surah al-Hujuraat verse 13 has high relevance in the context of modern society. As part of universal revelation, the Qur'an offers a wise approach on diversity and social relations. The message contained in this verse directing humanity to build bridges of brotherhood and strengthen human ties, regardless of cultural background or ethnicity.